Study on Kinetic and Optimization of Continuous Advanced Oxidative Decolorization of Brilliant Reactive Red Dye - M. Hameed, Forqan; M. Mousa, Khalid (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
The azo dye brilliant reactive red K-2BP (λmax = 534 nm) is widely used for coloring textiles because of its low-cost and tolerance fastness properties. Wastewaters treatment that contains the dye by conventional ways is usually inadequate due to its resistance to biological and chemical degradation. During this study, the continuous reactor of an advanced oxidation method supported the use of H2O2/sunlight, H2O2/UV, H2O2/TiO2/sunlight, and H2O2/TiO2/UV for decolorization of brilliant reactive red dye from the effluent. The existence of an optimum pH, H2O2 concentration, TiO2 concentration, and dye concentration was taken from the batch reactor experiments. The best conditions were pH=3, H2O2 dosage = 500 ppm, TiO2=100ppm and dye concentration=15 ppm .Under the most effective conditions, complete removal of the dye solution was achieved with different flow rates (10, 30, 60) ml/min. At flow rate of 10 ml/min, the percentage of decolorization were (80.47%, 84.65%, 89.42%, 77.5%) and at 60 mL/min (65.19%, 68.26%, 70.01%, 56.8%) for H2O2/sunlight, H2O2/UV, H2O2/TiO2/sunlight and H2O2/TiO2/UV respectively. Results of degradation information showed that the decolorization method was pseudo-first-order kinetics.